Narasi Religius tentang Alam dan Pengaruhnya terhadap Perilaku Ekonomi Berkelanjutan Masyarakat - Umar Mukhtar Siregar; Hidayat Herman (Management Studies and Business journal, 2025)
This study investigates how religious narratives about nature shape sustainable economic behavior within local communities. Environmental degradation and economic vulnerability require approaches that integrate ethical values with everyday economic practices. Using a qualitative case study design, data were collected through observation, in-depth interviews, and document analysis involving religious leaders, educators, and local economic actors. The findings indicate that religious narratives construct nature as a moral trust and frame environmentally friendly practices as forms of spiritual responsibility. These narratives influence economic decision-making by guiding choices in production and consumption, particularly through themes of moral accountability, balance, and collective welfare. The study also reveals a tension between normative religious commitments and market pressures, which limits the translation of moral narratives into consistent sustainable practices, especially at the production level. This research demonstrates that religious narratives function not only as moral discourse but also as symbolic mechanisms that mediate between environmental ethics and economic behavior. The novelty of this study lies in integrating narrative analysis with the study of sustainable economic behavior, offering an interpretive framework that explains how symbolic meanings influence material economic choices. The findings contribute to interdisciplinary debates on religion, discourse, and sustainable development by highlighting the role of meaning-making processes in shaping.